Ethics and Drug Resistance: Collective Responsibility for Global Public Health - Jamrozik, Euzebiusz; Selgelid, Michael (Public Health Ethics Analysis, 2020)
This Open Access volume provides in-depth analysis of the wide range of ethical issues associated with drug-resistant infectious diseases. Antimicrobial resistance (AMR) is widely recognized to be one of the greatest threats to global public health in coming decades; and it has thus become a major topic of discussion among leading bioethicists and scholars from related disciplines including economics, epidemiology, law, and political theory. Topics covered in this volume include responsible use of antimicrobials; control of multi-resistant hospital-acquired infections; privacy and data collection; antibiotic use in childhood and at the end of life; agricultural and veterinary sources of resistance; resistant HIV, tuberculosis, and malaria; mandatory treatment; and trade-offs between current and future generations. As the first book focused on ethical issues associated with drug resistance, it makes a timely contribution to debates regarding practice and policy that are of crucial importance to global public health in the 21st century.